Mexicans with Sweaters, Working in the Oil/Tar Sands, In Newfoundland’s Third Largest City: Regionalism, Narrative, and Imagination in Fort McMurray, (Texas?) - Thorne, Cory (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2012)
Northern Alberta is a space of conflict, not only in terms of environmental politics, but likewise in terms of regional identity and community sustainability. Using a variety of forms of narrative (drawing from mediated and unmediated sources in image, text, and sound), we can reveal the dominant cultural imaginaries that frame and limit our abilities to progress beyond these conflicts. This is a study of regionalism, nationalism, and identity in a city divided between an imagined Albertan conservatism, a displaced Newfoundland outport, and a cosmopolitan global work-force. It is a study of narrative in everyday life, in an effort to deconstruct divisive attitudes in acknowledgement of a more complex and diverse reality.